2019
DOI: 10.1136/bmjgh-2018-001157
|View full text |Cite
|
Sign up to set email alerts
|

Assessing global preparedness for the next pandemic: development and application of an Epidemic Preparedness Index

Abstract: IntroductionRobust metrics for national-level preparedness are critical for assessing global resilience to epidemic and pandemic outbreaks. However, existing preparedness assessments focus primarily on public health systems or specific legislative frameworks, and do not measure other essential capacities that enable and support public health preparedness and response.MethodsWe developed an Epidemic Preparedness Index (EPI) to assess national-level preparedness. The EPI is global, covering 188 countries. It con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(175 citation statements)
references
References 29 publications
2
149
0
3
Order By: Relevance
“…21 Other indirect consequences of previous infectious disease outbreaks include less healthcare utilisation and limited capacity for public health surveillance. [22][23][24] These impacts can persist long after the disease outbreak is contained. 25 However, much of the evidence available about these impacts on maternal and newborn health is either modelled or is from studies using secondary data such as population-based surveys and routine health management information system analysis.…”
Section: Introductionmentioning
confidence: 99%
“…21 Other indirect consequences of previous infectious disease outbreaks include less healthcare utilisation and limited capacity for public health surveillance. [22][23][24] These impacts can persist long after the disease outbreak is contained. 25 However, much of the evidence available about these impacts on maternal and newborn health is either modelled or is from studies using secondary data such as population-based surveys and routine health management information system analysis.…”
Section: Introductionmentioning
confidence: 99%
“… 11–13 A similar metric is the Epidemic Preparedness Index tool, also published in 2019 but with fewer countries and indicators included. 14 This present paper focuses on the GHSI.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported improvements in disease surveillance in the African countries as a result of lessons learned from the 2014-2016 West Africa EVD outbreak [17][18][19][20]. Oppenheim et al [21] noted that West and Central African countries still have the lowest epidemic preparedness index. The latter assesses the capacity of institutions to detect, report and respond to outbreaks.…”
Section: Epidemiology and Infectionmentioning
confidence: 99%